Between theory and empiria. Semiotics as a descriptive methodology for social sciences - Mattozzi, Alvise (E|C, 2020)
The present contribution points to the primary methodological character of semiotics as the main reason for the difficulties that semiotics has in dialoguing with social sciences, which should be its main interlocutors. For this reason, the contribution invites to cultivate and extend the methodological level, in order to assert its relevance for the reflection and action of all social sciences and thus creating a space, where semiotics can actually develop in collaboration with other social sciences. Then, the present contribution urges semioticians to stop the slow flaking, carried out during the last 20 years within the very semiotic field, of the four levels that structure semiotics’ disciplinary architecture, as established by Algirdas J. Greimas.